La Pathologie de la Guerre et la Pédagogie de la Paix chez Thucydide - Hourdakis, Antoine (Études helléniques / Hellenic Studies, 1998)
In ancient Greece, war was considered a standard situation that was occasionally interrupted by peace. On one hand the following may be considered as aspects of the phenomenon of war: a) the manifestations of violence between rival groups and b) the armed conflicts between organized states, while forms of this phenomenon, according to Thucydides would be: a) dissension and b) fighting. On the other hand, we could reflect on the phenomenon of peace as: a) the status of harmony, order, equilibrium and of calm between different socio-political forces, b) the status of tranquility and serenity in all sorts of human activities and c) the prosperity and the happiness of individuals, social groups and states. According to the historian, war seems to be a malady of human nature for which he tries to find the origin and the symptoms. Hence, history is not viewed as a simple lesson of morality but rather as a practical and scientific one, a diachronically study of human psychology. Therefore, the amelioration of human mentality, thought and behavior depends mainly on the development and education of human beings.